Method for producing positive electrode active material and positive electrode active material

JP7632947B2Active Publication Date: 2025-02-19LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023533758
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-11
Filing Date
2022-01-11
Publication Date
2025-02-19
Estimated Expiration
2042-01-11

AI Technical Summary

Benefits of technology

【0015】 本発明によると、正極活物質の製造時に、アルミニウムを仮焼成(一次焼成)の後、水洗前の焼成(二次焼成)ステップで投入して最外縁の表面に存在するアルミニウムのドーピング程度を調節することで、製造される正極活物質が適用された電池の高温寿命特性、高温抵抗特性および高温ガス発生特性を改善することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632947000004
    Figure 0007632947000004
  • Figure 0007632947000005
    Figure 0007632947000005
  • Figure 0007632947000006
    Figure 0007632947000006
Patent Text Reader

Abstract

The present invention relates to a method for producing a cathode active material, the method including the steps of: (A) primarily firing a mixture of a cathode active material precursor having a composition represented by Chemical Formula 1-1 or 1-2 described herein and a lithium-containing raw material, to produce a pre-fired product; (B) mixing the pre-fired product with an aluminum-containing raw material, subjecting the mixture to secondary firing, followed by washing with water and drying, to produce a lithium transition metal oxide having a composition represented by Chemical Formula 2 described herein; and (C) dry-mixing the lithium transition metal oxide with a boron-containing raw material and heat-treating the mixture to form a coating layer; the cathode active material produced by the method; and a lithium secondary battery positive electrode and lithium secondary battery each including the cathode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0003193, filed on January 11, 2021, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, a positive electrode active material produced by the method, and a positive electrode for a lithium secondary battery and a lithium secondary battery each containing the positive electrode active material. [Background technology]

[0003] With the technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among these secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] Lithium transition metal oxides are used as the positive electrode active material for lithium secondary batteries, and among them, lithium cobalt oxide LiCoO2, which has high working voltage and excellent capacity characteristics, is mainly used. However, LiCoO2 has very poor thermal properties due to the instability of its crystal structure caused by delithiation, and is expensive, so there are limitations to its mass use as a power source in fields such as electric vehicles.

[0005] As a material to be used in place of LiCoO2, lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), lithium nickel composite metal oxides (LiNiO2, etc.), etc. have been developed. Among them, research and development of lithium nickel composite metal oxides, which have a high reversible capacity of about 200 mAh / g and therefore can easily be used to realize large-capacity batteries, has been actively carried out. However, LiNiO2 has inferior thermal stability compared to LiCoO2, and if an internal short circuit occurs due to external pressure in a charged state, the positive electrode active material itself decomposes, causing the battery to explode and catch fire. Therefore, as a method for maintaining the excellent reversible capacity of LiNiO2 and improving its low thermal stability, LiNiO2, which has a part of the nickel substituted with cobalt, has been developed. 1-α Co α Lithium-nickel composite metal oxides have been developed in which O2 (α = 0.1 to 0.3) or part of the nickel is replaced with Mn, Co, or Al.

[0006] However, the lithium nickel composite metal oxide has a problem of low capacity. In order to increase the capacity of the lithium nickel composite metal oxide, a method of increasing the content of nickel contained in the lithium nickel composite metal oxide has been studied, but in this case, a water washing process is necessary due to the presence of unreacted residual lithium on the surface, and the water washing process causes surface defects of the positive electrode active material, thereby reducing the life characteristics of the battery.

[0007] To solve this problem, research has been conducted on a method of forming a coating layer on the surface of a positive electrode active material at a low temperature after washing the positive electrode active material with water. However, there are still limitations in terms of improving high-temperature life characteristics, resistance characteristics, and high-temperature gas generation characteristics.

[0008] Therefore, there is a demand for the development of a positive electrode active material that not only has high capacity characteristics, but also has improved high-temperature life characteristics, high-temperature resistance characteristics, and high-temperature gas generation characteristics. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a method for producing a positive electrode active material having not only high capacity characteristics but also improved high-temperature life characteristics, high-temperature resistance characteristics and high-temperature gas generation characteristics, and a positive electrode active material produced thereby.

[0010] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned can be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0011] In order to solve the above problems, the present invention provides a method for producing a cathode active material, the method including: (A) primarily firing a mixture of a cathode active material precursor having a composition represented by the following chemical formula 1-1 or 1-2 and a lithium-containing raw material to produce a pre-fired product; (B) mixing the pre-fired product with an aluminum-containing raw material, subjecting the mixture to a second firing, followed by washing with water and drying to produce a lithium transition metal oxide having a composition represented by the following chemical formula 2; and (C) dry-mixing the lithium transition metal oxide with a boron-containing raw material, followed by heat treatment to form a coating layer. [Chemical formula 1-1] Ni a1 Co b1 Mn c1 M 1 d1 (OH)2 [Chemical formula 1-2] Ni a1 Co b1 Mn c1 M 1 d1 O.H. In the above chemical formulas 1-1 and 1-2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.7≦a1≦1.0, 0≦b1≦0.3, 0≦c1≦0.3, 0≦d1≦0.1, [Chemical formula 2] Li x Ni a2 Co b2 Mn c2 Al d2 M 1 e2 O2 In the above Chemical Formula 2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.9≦x≦1.12, 0.7≦a2≦1.0, 0≦b2≦0.3, 0≦c2≦0.3, 0 <d2≦0.2、0≦e2≦0.1である。

[0012] The present invention also provides a lithium transition metal oxide represented by the following chemical formula 2, and a coating layer containing boron formed on the surface of the lithium transition metal oxide, the coating layer containing Li-Al-BO solid solution, and a peak intensity detected at a mass of more than 27.0 and not more than 27.5 in a time-of-flight secondary ion mass spectrometry spectrum and an Al + The present invention provides a positive electrode active material in which the ratio of the peak intensities of the above is 1:0.5 to 1:1.5. [Chemical formula 2] Li x Ni a2 Co b2 Mn c2 Al d2 M 1 e2 O2 In the above Chemical Formula 2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.9≦x≦1.12, 0.7≦a2≦1.0, 0≦b2≦0.3, 0≦c2≦0.3, 0 <d2≦0.2、0≦e2≦0.1である。

[0013] The present invention also provides a positive electrode for a lithium secondary battery, comprising the positive electrode active material according to the present invention.

[0014] The present invention also provides a lithium secondary battery comprising the positive electrode according to the present invention. Effect of the Invention

[0015] According to the present invention, when preparing a positive electrode active material, aluminum is added in a step of pre-baking (primary baking) and then baking (secondary baking) before washing with water to adjust the degree of doping of aluminum present on the outermost surface, thereby improving the high temperature life characteristics, high temperature resistance characteristics, and high temperature gas generation characteristics of a battery using the prepared positive electrode active material. [Brief description of the drawings]

[0016] [Figure 1] 1 shows the results of cation spectrum analysis of the positive electrode active materials of Example 1 and Comparative Example 1. [Diagram 2] 1 shows the results of anion spectrum analysis of the positive electrode active materials of Example 1 and Comparative Example 1. [Diagram 3] 1 is a graph showing data related to the discharge capacity at high temperatures of the secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 4] 2 is a graph showing high-temperature life characteristics of secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2. [Diagram 5] 2 is a graph showing high-temperature resistance characteristics of secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 6] 2 is a graph showing high-temperature gas generation characteristics of secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will now be described in more detail.

[0018] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0019] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless it has a clearly different meaning in the context.

[0020] In this specification, the terms "including," "comprising," or "having" are intended to indicate the presence of implemented features, numerals, steps, components, or combinations thereof, and should be understood as not precluding the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0021] In this specification, "%" means % by weight unless expressly indicated otherwise.

[0022] As used herein, the term "on" is meant to include not only when one structure is formed immediately on top of another structure, but also when a third structure is interposed between the structures.

[0023] Method for producing positive electrode active material The method for producing a positive electrode active material according to the present invention will now be described in detail.

[0024] The method for producing a positive electrode active material according to the present invention includes the steps of: (A) primarily firing a mixture of a positive electrode active material precursor having a composition represented by the following Chemical Formula 1-1 or 1-2 and a lithium-containing raw material to produce a pre-fired product; (B) mixing the pre-fired product with an aluminum-containing raw material, secondary firing the mixture, and then washing and drying the mixture to produce a lithium transition metal oxide having a composition represented by the following Chemical Formula 2; and (C) dry-mixing the lithium transition metal oxide with a boron-containing raw material and heat-treating the mixture to form a coating layer. [Chemical formula 1-1] Ni a1 Co b1 Mn c1 M 1 d1 (OH)2 [Chemical formula 1-2] Ni a1 Co b1 Mn c1 M 1 d1 O.H. In the above Chemical Formulas 1-1 and 1-2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.7≦a1≦1.0, 0≦b1≦0.3, 0≦c1≦0.3, 0≦d1≦0.1, [Chemical formula 2] Li x Ni a2 Co b2 Mn c2 Al d2 M 1 e2 O2 In the above Chemical Formula 2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.9≦x≦1.12, 0.7≦a2≦1.0, 0≦b2≦0.3, 0≦c2≦0.3, 0 <d2≦0.2、0≦e2≦0.1である。

[0025] The present inventors have discovered that by adding aluminum in the secondary firing (firing before washing) step rather than the primary firing (pre-firing) step during the preparation of a positive electrode active material, and adjusting the degree of doping of aluminum present on the outermost surface to a high level, it is possible to improve the high temperature life characteristics, high temperature resistance characteristics, and high temperature gas generation characteristics of a battery using the prepared positive electrode active material.

[0026] Each step will be described in more detail below.

[0027] (A) Step Step (A) is a step of primarily firing a mixture of a positive electrode active material precursor having the composition of the following chemical formula 1-1 or 1-2 and a lithium-containing raw material to produce a pre-fired product.

[0028] [Chemical formula 1-1] Ni a1 Co b1 Mn c1 M 1 d1 (OH)2

[0029] [Chemical formula 1-2] Ni a1 Co b1 Mn c1 M 1 d1 O.H.

[0030] In the above chemical formulas 1-1 and 1-2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.7≦a1≦1.0, 0≦b1≦0.3, 0≦c1≦0.3, and 0≦d1≦0.1.

[0031] The a1 means the atomic fraction of nickel among the metal elements in the precursor, and may be 0.7≦a1<1, 0.7≦a1≦0.98, or 0.7≦a1≦0.95.

[0032] The b1 means the atomic fraction of cobalt among the metal elements in the precursor, and is 0 <b1≦0.3または0.01≦b1≦0.3であることができる。

[0033] The c1 represents the atomic fraction of manganese among the metal elements in the precursor, and is 0 <c1≦0.3または0.01≦c1≦0.3であることができる。

[0034] The d1 is the metal element M in the precursor. 1 and may be 0≦d1≦0.1 or 0≦d1≦0.05.

[0035] The lithium-containing raw material may include at least one selected from lithium hydroxide hydrate, lithium carbonate, and lithium hydroxide. Specifically, the lithium-containing raw material may be lithium hydroxide hydrate, more specifically, LiOH·H2O. In this case, the reactivity of the lithium-containing raw material with a precursor having a high atomic fraction of nickel among metal elements in the precursor may be improved.

[0036] The positive electrode active material precursor and the lithium-containing raw material may be mixed in a molar ratio of 1:1.0 to 1:1.10, specifically 1:1.03 to 1:1.09, more specifically 1:1.05 to 1:1.09. If the lithium-containing raw material is mixed in an amount less than this range, the capacity of the positive electrode active material to be manufactured may decrease, and if the lithium-containing raw material is mixed in an amount exceeding this range, a large amount of unreacted Li may remain as a by-product, resulting in a decrease in capacity and separation of positive electrode active material particles after firing (induction of agglomeration phenomenon of the positive electrode active material).

[0037] The primary firing temperature may be 600° C. to 775° C. Specifically, the primary firing temperature may be 620° C. to 760° C., and more specifically, 620° C. to 700° C. When the primary firing temperature is within the above range, the crystal structure of the pre-fired product can be adjusted, and as a result, the diffusion of aluminum during the secondary firing can be appropriately adjusted.

[0038] The primary firing can be carried out in an oxygen atmosphere, in which case a pre-fired product having a structurally stable phase can be formed.

[0039] The primary firing can be performed for 2 to 15 hours. Specifically, the firing can be performed for 3 to 10 hours, and more specifically, for 3 to 8 hours. When the primary firing time is within the above range, firing can be performed well without unevenness (uniformity) at each firing position.

[0040] The pre-calcined product has unreacted residual lithium on the surface, and the amount of such residual lithium can be minimized through steps (B) and (C) according to the present invention.

[0041] (B) Step Step (B) is a step of mixing the pre-calcined product produced in step (A) with an aluminum-containing raw material, subjecting the mixture to secondary calcination, and then washing and drying to produce a lithium transition metal oxide having the composition of the following chemical formula 2.

[0042] [Chemical formula 2] Li x Ni a2 Co b2 Mn c2 Al d2 M 1 e2 O2

[0043] In the above Chemical Formula 2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.9≦x≦1.12, 0.7≦a2≦1.0, 0≦b2≦0.3, 0≦c2≦0.3, 0 <d2≦0.2、0≦e2≦0.1である。

[0044] The a2 means the atomic fraction of nickel among metal elements other than lithium in the positive electrode active material, and may be 0.7≦a2<1.0, 0.7≦a2≦0.98, or 0.7≦a2≦0.95.

[0045] The b2 represents the atomic fraction of cobalt among the metal elements other than lithium in the positive electrode active material, and is 0 <b2≦0.3または0.01≦b2≦0.3であることができる。

[0046] The c2 represents the atomic fraction of manganese among the metal elements other than lithium in the positive electrode active material, and is 0 <c2≦0.3または0.01≦c2≦0.3であることができる。

[0047] The d2 refers to the atomic fraction of aluminum among metal elements other than lithium in the positive electrode active material, and may be 0≦d2≦0.2, 0≦d2≦0.1, or 0≦d2≦0.05.

[0048] The e2 is M among the metal elements other than lithium in the positive electrode active material. 1 and may be 0≦e2≦0.1 or 0≦e2≦0.05.

[0049] In the present invention, by mixing the aluminum-containing raw material and secondary firing in step (B), a coating layer containing aluminum at a high concentration is formed on the surface of the resulting positive electrode active material, and therefore the high-temperature life characteristics, high-temperature resistance characteristics, and high-temperature gas generation characteristics of a secondary battery including the positive electrode active material can be improved.

[0050] The aluminum-containing raw material may be one or more selected from Al(OH)3, Al2O3, AlF3, AlBr3, AlPO4, AlCl3, Al(NO3)3, Al(NO3)3·9H2O, Al2(SO4)3·H2O, Al(H2PO4)3, C2H5O4Al, Al2(SO4)3, NaAlO2, Al2CoO4, LaAlO3, and MgAl2O4. The aluminum-containing raw material may be specifically Al(OH)3, Al2O3, and more specifically Al(OH)3. In this case, the melting point of the aluminum-containing raw material is low, so that aluminum can be uniformly diffused and abundantly present on the surface side of the lithium transition metal oxide.

[0051] The aluminum-containing raw material may be added to the calcined product in an amount of 1,000 ppm to 10,000 ppm, specifically 2,000 ppm to 8,000 ppm, and more specifically 4,000 ppm to 6,000 ppm. When the content of the aluminum-containing raw material is within the above range, when the prepared cathode active material is applied to a battery, not only is a decrease in the battery capacity prevented, but thermal stability is also improved.

[0052] The secondary firing temperature may be 730° C. to 900° C. Specifically, the secondary firing temperature may be 730° C. to 850° C., and more specifically, 750° C. to 800° C. When the secondary firing temperature is within the above range, an appropriate crystal size is formed, and when the produced positive electrode active material is applied to a battery, the life characteristics of the battery can be improved.

[0053] The secondary firing temperature is higher than the primary firing temperature, and the difference between the secondary firing temperature and the primary firing temperature may be 10° C. to 150° C., specifically 20° C. to 150° C., and more specifically 30° C. to 140° C. When the difference between the secondary firing temperature and the primary firing temperature is within the above range, it may be advantageous to control the degree of doping of aluminum present on the outermost surface.

[0054] The secondary firing can be performed in an oxygen atmosphere, which suppresses cation exchange between lithium and nickel, and improves the capacity of a battery when the produced positive electrode active material is used in the battery.

[0055] The secondary firing can be performed for 2 to 15 hours. Specifically, the firing can be performed for 3 to 10 hours, and more specifically, for 3 to 8 hours. When the secondary firing time is within the above range, firing can be performed well without unevenness (uniformity) at each firing position.

[0056] The water washing is a process for removing unreacted residual lithium, and is a process in which the secondary fired product is mixed with a water washing solution for washing, and then the secondary fired product is separated from the water washing solution.

[0057] The washing solution may be water, ethanol, etc., but is not limited thereto.

[0058] The washing solution may be mixed in an amount of 60 to 200 parts by weight, specifically 60 to 150 parts by weight, and more specifically 80 to 120 parts by weight, based on 100 parts by weight of the secondary sintered product. When the amount of the washing solution is within the above range, the residual lithium present on the surface of the secondary sintered product can be easily removed. When the amount of the washing solution is lower than the above range, the amount of the residual lithium present on the surface of the secondary sintered product is high, and gas may be generated when the secondary sintered product is applied to a battery. Conversely, when the amount of the washing solution is higher than the above range, the surface of the lithium transition metal oxide is damaged, and when the secondary sintered product is applied to a battery, the life span may be shortened and the resistance increase rate may be increased.

[0059] The step of separating the secondary fired product from the washing solution can be performed so that the moisture content of the secondary fired product separated from the washing solution is 3% to 15%. Specifically, the moisture content of the secondary fired product can be 5% to 12%, more specifically, 5% to 10%.

[0060] Here, the moisture content means the amount of moisture contained in the secondary fired product after being separated from the washing solution and before being dried, and can be calculated by the following Equation 1.

[0061] [Formula 1] Moisture content (%) = {[(mass of secondary fired product before drying) - (mass of secondary fired product after drying)] / (mass of secondary fired product before drying)} x 100

[0062] In this case, the drying may be performed by drying the secondary fired product separated from the washing solution at 130° C. for 300 minutes.

[0063] When the moisture content is within the above range, the surface state, i.e., the physical properties of the surface, are controlled, and the lithium transition metal oxide can easily coat the surface with a coating layer having a uniform composition and thickness.

[0064] The separation can be carried out using a reduced pressure filter having an average pore size of 1 μm to 50 μm, in which case the secondary baked product can be separated from the washing solution in a short time.

[0065] The drying is for removing moisture from the lithium transition metal oxide that has been subjected to a water washing process, and can be carried out at 60° C. to 150° C. after removing moisture using a vacuum pump. Specifically, the drying can be carried out at a temperature of 60° C. to 150° C. for 3 hours or more.

[0066] (C) Step Step (C) is a step of dry-mixing the lithium transition metal oxide prepared in step (B) with a boron-containing raw material, followed by heat treatment to form a coating layer.

[0067] In step (C), a coating layer containing boron is formed on the surface of the lithium transition metal oxide. Specifically, a coating layer containing Li-Al-BO solid solution is formed on the surface of the lithium transition metal oxide. That is, when the lithium transition metal oxide and the boron-containing raw material are dry-mixed and heat-treated, a coating layer containing not only Li-BO solid solution but also Li-Al-BO solid solution is formed. In this case, the coating layer is strengthened and the side reaction between the positive electrode active material and the electrolyte can be more effectively suppressed. Furthermore, the coating layer can further contain Ni-Co-Mn-Al solid solution rich in aluminum and Ni-Co-Mn-Al-B solid solution rich in aluminum. Meanwhile, the thickness of the coating layer can be 4 nm to 10 nm. When the thickness of the coating layer is within the above range, the surface side reaction can be suppressed, and when applied to a battery, the life characteristics of the battery can be improved and gas generation can be suppressed.

[0068] In addition, since aluminum is abundant on the outermost surface of the lithium transition metal oxide, aluminum is also abundant in the coating layer. As a result, when the produced positive electrode active material is analyzed, the intensity of the peak detected at a mass of more than 27.0 and not more than 27.5 in the time-of-flight secondary ion mass spectrometry spectrum and the Al + The ratio of the intensities of the peaks can be 1:0.5 to 1:1.5.

[0069] The boron-containing source material may be one or more selected from H3BO3, B2H4O4, B2O3, LiBO2, Li2B4O7, and AlBO3. The boron-containing source material may be specifically H3BO3, B2O3, and more specifically H3BO3. In this case, the melting point of the boron-containing source material is low, and a uniform coating layer may be formed.

[0070] The boron-containing raw material may be mixed in an amount of 0.1 to 1.5 parts by weight, specifically 0.2 to 1.0 parts by weight, and more specifically 0.4 to 0.8 parts by weight, based on 100 parts by weight of the lithium transition metal oxide. When the content of the boron-containing raw material is within the above range, a coating layer is not only formed uniformly but also has an appropriate thickness, so that when the prepared cathode active material is applied to a battery, the life characteristics of the battery can be improved.

[0071] Dry mixing of the lithium transition metal oxide and the boron-containing raw material is advantageous in that impurities can be minimized compared to wet mixing.

[0072] The heat treatment temperature may be 250°C to 400°C. The heat treatment temperature may be specifically 250°C to 350°C, and more specifically 260°C to 330°C. When the heat treatment temperature is within the above range, a coating layer is uniformly formed on the lithium transition metal oxide, and when applied to a battery, the life characteristics of the battery can be improved. On the other hand, when the heat treatment temperature is lower than the lower limit of the above range, the reactivity of the boron-containing raw material is low, and the boron-containing raw material may remain on the surface of the lithium transition metal oxide and act as a resistor, whereas when the heat treatment temperature is higher than the upper limit of the above range, the lithium present on the surface of the lithium transition metal oxide may over-react with the boron-containing raw material, resulting in a large amount of lithium being present in the coating layer.

[0073] positive electrode active material In addition, the positive electrode active material according to the present invention includes a lithium transition metal oxide represented by the following Chemical Formula 2, and a coating layer containing boron formed on a surface of the lithium transition metal oxide, the coating layer including Li-Al-BO solid solution, and the intensity of a peak detected at a mass of more than 27.0 and not more than 27.5 in a time-of-flight secondary ion mass spectrometry spectrum of the positive electrode active material is greater than or equal to Al + The ratio of the peak intensities is 1:0.5 to 1:1.5.

[0074] [Chemical formula 2] Li x Ni a2 Co b2 Mn c2 Al d2 M 1 e2 O2

[0075] In the above Chemical Formula 2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.9≦x≦1.12, 0.7≦a2≦1.0, 0≦b2≦0.3, 0≦c2≦0.3, 0 <d2≦0.2、0≦e2≦0.1である。

[0076] The a2 means the atomic fraction of nickel among metal elements other than lithium in the positive electrode active material, and may be 0.7≦a2<1.0, 0.7≦a2≦0.98, or 0.7≦a2≦0.95.

[0077] The b2 represents the atomic fraction of cobalt among the metal elements other than lithium in the positive electrode active material, and is 0 <b2≦0.3または0.01≦b2≦0.3であることができる。

[0078] The c2 represents the atomic fraction of manganese among the metal elements other than lithium in the positive electrode active material, and is 0 <c2≦0.3または0.01≦c2≦0.3であることができる。

[0079] The d2 refers to the atomic fraction of aluminum among metal elements other than lithium in the positive electrode active material, and may be 0≦d2≦0.2, 0≦d2≦0.1, or 0≦d2≦0.05.

[0080] The e2 is M among the metal elements other than lithium in the positive electrode active material. 1 and may be 0≦e2≦0.1 or 0≦e2≦0.05.

[0081] The positive electrode active material is manufactured by the above-mentioned manufacturing method, and has a coating layer reinforced by the presence of a large amount of aluminum on the surface, and can improve the high-temperature life characteristics, high-temperature resistance characteristics, and high-temperature gas generation characteristics of a secondary battery including the positive electrode active material. The coating layer can further include an aluminum-rich Ni-Co-Mn-Al solid solution and an aluminum-rich Ni-Co-Mn-Al-B solid solution. Meanwhile, the thickness of the coating layer can be 4 nm to 10 nm. When the thickness of the coating layer is within the above range, side reactions with the electrolyte can be suppressed, and when applied to a battery, the high-temperature life characteristics and high-temperature resistance characteristics of the battery can be improved and gas generation can be suppressed.

[0082] The intensity of a peak detected at a mass of more than 27.0 and not more than 27.5 in a time-of-flight secondary ion mass spectrometry spectrum of the positive electrode active material and Al + The ratio of the peak intensities is 1:0.5 to 1:1.5, specifically 1:0.6 to 1:1.3, and more specifically 1:0.7 to 1:1.2. The peak detected at a mass greater than 27 and equal to or less than 27.5 is C2H3 + In this case, not only the capacity characteristics but also the cycle characteristics of the battery to which the positive electrode active material according to the present invention is applied can be improved. In particular, the high-temperature life characteristics of the battery can be improved, and the resistance increase rate and the amount of gas generation at high temperatures can be suppressed.

[0083] The ratio of the intensity of the peak detected at masses 182 to 184 in a time-of-flight secondary ion mass spectrometry spectrum of the positive electrode active material to the intensity of the peak detected at masses 172 to 174 may be 1:0.3 to 1:2, specifically 1:0.4 to 1:1.5, and more specifically 1:0.5 to 1:1.2. In this case, side reactions that may occur on the surface of the positive electrode active material are suppressed, gas generation during charging and discharging of a secondary battery including the positive electrode active material can be suppressed, and the resistance increase rate of the secondary battery can be improved.

[0084] The ratio of the intensity of the peak detected at masses 182 to 184 in the time-of-flight secondary ion mass spectrometry spectrum of the positive electrode active material to the intensity of the peak detected at masses 197 to 199 may be 1:0.3 to 1:1.5, specifically 1:0.3 to 1:1.2, and more specifically 1:0.3 to 1:0.8. In this case, side reactions that may occur on the surface of the positive electrode active material are suppressed, gas generation during charging and discharging of a secondary battery including the positive electrode active material can be suppressed, and the resistance increase rate of the secondary battery can be improved.

[0085] positive electrode The present invention also provides a positive electrode for a lithium secondary battery comprising the positive electrode active material according to the present invention. Specifically, the positive electrode for the secondary battery comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, the positive electrode active material layer comprising the positive electrode active material according to the present invention.

[0086] Here, since the positive electrode active material is the same as that described above, detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0087] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0088] The positive electrode active material layer may contain, in addition to the positive electrode active material, a conductive material and, if necessary, optionally a binder.

[0089] In this case, the positive electrode active material may be included in an amount of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in the above content range, excellent capacity characteristics can be exhibited.

[0090] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 0.1% by weight to 15% by weight based on the total weight of the positive electrode active material layer.

[0091] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1% by weight to 15% by weight based on the total weight of the positive electrode active material layer.

[0092] The positive electrode can be manufactured by a general method for manufacturing a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode can be manufactured by applying a composition for forming a positive electrode active material layer, which is prepared by dissolving or dispersing the positive electrode active material described above and, optionally, a binder and a conductive material in a solvent, onto the entire positive electrode assembly, followed by drying and rolling.

[0093] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination of two or more of these. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the manufacture of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.

[0094] As another method, the positive electrode can also be produced by casting the composition for forming a positive electrode active material layer on another support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0095] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0096] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0097] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0098] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0099] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0100] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0101] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, the carbon material may be either low-crystalline carbon or high-crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0102] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0103] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and can be added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0104] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0105] For example, the negative electrode active material layer can be produced by applying a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the composition. Alternatively, the negative electrode active material layer can be produced by casting the composition for forming a negative electrode active material layer onto a separate support, peeling it off from the support, and laminating the resulting film onto the negative electrode current collector.

[0106] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc., can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.

[0107] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0108] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0109] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among them, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.

[0110] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0111] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, in order to improve the life characteristics of the battery, suppress the decrease in the capacity of the battery, and improve the discharge capacity of the battery. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0112] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0113] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0114] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0115] The shape of the lithium secondary battery is not particularly limited, but may be a cylindrical type using a can, a square type, a pouch type, a coin type, or the like.

[0116] The lithium secondary battery is not only used as a battery cell that is used as a power source for small devices, but can also be preferably used as a unit battery in a medium- to large-sized battery module that includes a large number of battery cells.

[0117] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various other forms, and the scope of the present invention should not be interpreted as being limited to the examples described below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0118] Working Example Example 1 Positive electrode active material precursor Ni 0.88 Co 0.05 Mn 0.07 (OH)2 and LiOH·H2O were mixed so that the molar ratio of Li:transition metals (Ni+Co+Mn) was 1.07:1, and the mixture was first fired at 640℃ for 5 hours to obtain a pre-fired product (Ni 0.88 Co 0.05 Mn 0.07 O2) was produced.

[0119] The calcined product was mixed with Al(OH)3 so that the molar ratio of Ni:Co:Mn:Al was 0.86:0.05:0.07:0.02, and the mixture was subjected to secondary calcination at 775°C for 6 hours to obtain a calcined product (LiNi 0.86 Co 0.05 Mn 0.07 Al 0.02 The calcined product was mixed with water in a weight ratio of 1:1.2, washed with water for 5 minutes, filtered under reduced pressure until the water content was 5% to 10%, and then dried at 130°C to obtain LiNi 0.86 Co 0.05 Mn 0.07 Al 0.02 A lithium transition metal oxide having a composition of O2 was produced.

[0120] Next, the lithium transition metal oxide and HBO were mixed in a weight ratio of 100:0.57 and heat-treated at 300°C for 4 hours to prepare a positive electrode active material having a coating layer including Li-Al-BO solid solution, Li-BO solid solution, and BO solid solution formed on the surface.

[0121] Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that the primary baking temperature was adjusted to 720°C.

[0122] Comparative Example 1 Positive electrode active material precursor Ni 0.88 Co 0.05 Mn 0.07 (OH)2, LiOH·H2O, and Al(OH)3 were mixed so that the molar ratio of Li:Ni:Co:Mn:Al was 1.05:0.86:0.05:0.07:0.02, and the mixture was fired at 640℃ for 5 hours and then fired at 775℃ for 6 hours to obtain the fired product (LiNi 0.86 Co 0.05 Mn 0.07 Al 0.02 O2) was produced.

[0123] The calcined product was mixed with water in a weight ratio of 1:1.2 and washed for 5 minutes. The washed product was filtered under reduced pressure so that the water content of the washed product was 5% to 10%, and then dried at 130°C to obtain LiNi 0.86 Co 0.05 Mn 0.07 Al 0.02 A lithium transition metal oxide having a composition of O2 was produced.

[0124] Then, the lithium transition metal oxide and H3BO3 were mixed in a weight ratio of 100:0.57 and heat-treated at 300°C for 4 hours to prepare a positive electrode active material having a coating layer containing Li-BO and BO solid solution formed on the surface.

[0125] Comparative Example 2 Lithium transition metal oxide LiNi 0.88 Co 0.05 Mn 0.07 O2, H3BO3, and Al(OH)3 were mixed in a weight ratio of 100:0.2:0.3 and heat-treated at 700°C for 4 hours to prepare a positive electrode active material having a coating layer containing Li-Al-BO solid solution formed on the surface.

[0126] Experimental example 1: Confirmation of coating layer formation The cation and anion spectra of the surfaces of the positive electrode active materials produced in Example 1 and Comparative Example 1 were measured using a time-of-flight secondary ion mass spectrometer (TOF-SIMS5, manufactured by ION-TOF GmbH), and the results are shown in FIGS. 1 and 2.

[0127] First, (a) and (b) of FIG. 1 show the results of cation spectrum analysis of Example 1 and Comparative Example 1, respectively.

[0128] As a result of the cation analysis of the outermost surface of the positive electrode active material prepared in Example 1 and Comparative Example 1, in the case of Example 1, Al was detected in the region of 26.9 mass to 27.0 mass. + In contrast, in the case of Comparative Example 1, the peak of Al is strongly observed in the above region. +It can be seen that the peak of is weakly observed. This is because in Example 1, the preparation method was adjusted so that a large amount of aluminum was present on the surface of the positive electrode active material before the coating layer was formed on the surface of the positive electrode active material.

[0129] Specifically, the peak detected at a mass greater than 27.0 and less than or equal to 27.1 in the positive ion spectrum of Example 1 (C2H3 + Peak) and Al + It can be seen that the ratio of the peak intensities of the C2H3 and C2H4 is 1:0.9. In comparison, the peak (C2H3 + Peak) and Al + It can be confirmed that the ratio of the peak intensities is 1:0.2.

[0130] 2(a) and (b) show the results of negative ion spectrum analysis of Example 1 and Comparative Example 1, respectively.

[0131] As a result of anion analysis of the outermost surface of the positive electrode active materials prepared in Example 1 and Comparative Example 1, it can be confirmed that in Example 1, a peak related to aluminum is strongly observed in the 172 mass to 174 mass region and a peak related to aluminum is strongly observed in the 197 mass to 198 mass region, whereas in Comparative Example 1, the peaks are weakly observed in these regions.

[0132] Specifically, it can be confirmed that the ratio of the intensity of the peak detected at masses 182 to 184 to the intensity of the peak detected at masses 172 to 174 in the negative ion spectrum of Example 1 is 1:1.1, and the ratio of the intensity of the peak detected at masses 182 to 184 to the intensity of the peak detected at masses 197 to 199 is 1:0.5. In comparison, it can be confirmed that the ratio of the intensity of the peak detected at masses 182 to 184 to the intensity of the peak detected at masses 172 to 174 in the negative ion spectrum of Comparative Example 1 is 1:0.4, and the ratio of the intensity of the peak detected at masses 182 to 184 to the intensity of the peak detected at masses 197 to 199 is 1:0.2.

[0133] Experimental Example 2: Evaluation of capacity and resistance characteristics of lithium secondary batteries Lithium secondary batteries were manufactured using the positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, respectively, and their capacity and resistance characteristics were examined. In this regard, each lithium secondary battery was manufactured in the following manner, except that the positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, respectively, were used.

[0134] Specifically, the positive electrode active material, carbon black conductive material, and polyvinylidene fluoride binder prepared in each of Examples 1 and 2 and Comparative Examples 1 and 2 were mixed in a weight ratio of 97.5:1.15:1.35, and mixed in NMP solvent to prepare a positive electrode forming composition. The positive electrode forming composition was applied to an Al current collector having a thickness of 12 μm, dried, and roll-pressed to prepare a positive electrode. The positive and negative electrodes prepared above were laminated with lithium metal and a porous polyethylene separator, which were placed in a battery case, and an electrolyte solution in which 1M LiPF6 and other additives were dissolved in a mixed solvent of ethylene carbonate (EC): dimethyl carbonate (DMD): ethyl methyl carbonate (EMC) in a ratio of 3:4:3 was injected to prepare the lithium secondary batteries according to Examples 1 and 2 and Comparative Examples 1 and 2.

[0135] Each of the lithium secondary batteries prepared as described above was charged in CC / CV mode at a constant current of 0.1C at 25°C up to 4.25V (CV0.05C), and then discharged in CC mode down to 3V to measure the initial charge capacity (unit: mAh / g) at room temperature (25°C). The results are shown in Table 1 below.

[0136] [Table 1]

[0137] Referring to Table 1, it can be seen that the initial charge capacity at room temperature is excellent in the case of the batteries including the positive electrode active materials of Examples 1 and 2. For reference, when a coating layer is formed by mixing a boron-containing raw material and an aluminum-containing raw material with a lithium transition metal oxide and then heat-treating the mixture at 700°C as in Comparative Example 2, it can be seen that the degree of diffusion of aluminum and boron is not controlled, and some boron or aluminum is doped into the positive electrode active material at high temperatures, resulting in a reaction that reduces the capacity.

[0138] Each of the lithium secondary batteries manufactured as described above was charged in CC / CV mode at a constant current of 0.33 C at 45° C. up to 4.25 V (CV 0.05 C), and then discharged in CC mode down to 3 V. The above charge and discharge behavior was counted as one cycle, and this cycle was repeated 30 times. After that, the initial discharge capacity (unit: mAh / g), capacity retention rate (unit: %), and resistance increase rate (unit: %) at high temperature (45° C.) of each of the lithium secondary batteries manufactured as described above were measured, and the results are shown in Table 2 and FIGS. 3 to 5 below.

[0139] FIG. 3 is a graph showing data related to the discharge capacity at high temperatures of the secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2.

[0140] Fig. 4 is a graph showing the high-temperature life characteristics of the secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2. Specifically, Fig. 4 is a graph showing data related to capacity maintenance rate at high temperatures.

[0141] Fig. 5 is a graph showing the high-temperature resistance characteristics of the secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2. Specifically, Fig. 5 is a graph showing data relating to the rate of increase in resistance at high temperatures.

[0142] [Table 2]

[0143] As shown in Table 2 and FIGS. 3 to 5, the secondary batteries prepared in Examples 1 and 2 were found to be far superior in high temperature capacity characteristics, life characteristics, and resistance characteristics to the secondary batteries prepared in Comparative Examples 1 and 2.

[0144] Experimental example 3: Evaluation of gas generation rate Lithium secondary batteries were manufactured using the positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, respectively, and their capacity and resistance characteristics were examined. In this regard, each lithium secondary battery was manufactured in the following manner, except that the positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, respectively, were used.

[0145] Specifically, the positive electrode active materials, carbon black conductive material, and polyvinylidene fluoride binder prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were mixed in a weight ratio of 97.5:1.15:1.35, and mixed in NMP solvent to prepare a positive electrode composition. The positive electrode composition was applied to an Al current collector having a thickness of 12 μm, dried, and roll-pressed to prepare a positive electrode.

[0146] Next, the negative electrode active material (natural graphite), conductive material (carbon black) and binder (SBR+CMC) were mixed in water in a weight ratio of 95:1.5:3.5 to prepare a negative electrode slurry. The negative electrode slurry was applied onto a copper current collector, dried and then rolled to prepare a negative electrode.

[0147] The electrode assembly was prepared by interposing a separator between the positive and negative electrodes, and then placed inside a battery case, and an electrolyte was injected to prepare three monocells each having an electrode size of 3 cm x 4 cm. The electrolyte used was an organic solvent obtained by mixing ethylene carbonate: ethyl methyl carbonate: diethyl carbonate in a volume ratio of 3:3:4, in which 1 M LiPF6 was dissolved.

[0148] The three mono cells were charged in CC / CV mode at 45° C. with a constant current of 0.33 C to 4.25 V (CV 0.05 C), and the positive electrode was separated. The separated positive electrode was placed in a cell pouch, and the electrolyte was further injected and sealed to prepare a sample. The sample was stored at 60° C. for 4 weeks, and the cell volume change rate (unit: %) was measured, and the results are shown in Table 3 and FIG. 6 below.

[0149] [Table 3]

[0150] Referring to Table 3, it can be seen that in the case of the batteries including the positive electrode active materials of Examples 1 and 2, the cell volume change rate during storage at high temperature is significantly smaller than that of the batteries including the positive electrode active materials of Comparative Examples 1 and 2, and therefore the amount of gas generated is significantly smaller.

[0151] In other words, in the present invention, when manufacturing a positive electrode active material, aluminum is added in a step of pre-baking (primary baking) and then baking (secondary baking) before washing with water to adjust the doping degree of aluminum present on the outermost surface, thereby improving not only the capacity characteristics but also the cycle characteristics, especially the high-temperature life characteristics, of a battery using the manufactured positive electrode active material. In addition, it is possible to suppress an increase in resistance at high temperatures and the generation of gas at high temperatures of a battery using the positive electrode active material.

Claims

1. (A) preparing a pre-calcined product by primarily calcining a mixture of a positive electrode active material precursor having a composition represented by the following chemical formula 1-1 or 1-2 and a lithium-containing raw material; (B) mixing the calcined product with an aluminum-containing raw material, calcining the mixture, washing with water and drying to produce a lithium transition metal oxide having a composition represented by the following formula 2: (C) dry-mixing the lithium transition metal oxide and a boron-containing raw material and heat-treating the mixture to form a coating layer; The secondary firing temperature is higher than the primary firing temperature, and the difference between the secondary firing temperature and the primary firing temperature is 10° C. to 150° C. [Chemical formula 1-1] Ni a1 Co b1 Mn c1 M 1 d1 (OH) 2 [Chemical formula 1-2] Ni a1 Co b1 Mn c1 M 1 d1 O・OH In the above Chemical Formulas 1-1 and 1-2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.7≦a1≦1.0, 0≦b1≦0.3, 0≦c1≦0.3, and 0≦d1≦0.1, [Chemical formula 2] Li x Ni a2 Co b2 Mn c2 Al d2 M 1 e2 O 2 In the above Chemical Formula 2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.9≦x≦1.12, 0.7≦a2≦1.0, 0≦b2≦0.3, 0≦c2≦0.3, 0<d2≦0.2, and 0≦e2≦0.

1.

2. The method for producing a positive electrode active material according to claim 1, wherein the primary baking temperature is 600°C to 775°C.

3. The method for producing a positive electrode active material according to claim 1 or 2, wherein the secondary baking temperature is 730°C to 900°C.

4. The aluminum-containing source material is Al(OH). 3 , Al 2 O 3 , AlF 3 , AlBr 3 , AlPO 4 , AlCl 3 , Al(NO 3 ) 3 , Al(NO 3 ) 3 ・9H 2 O, Al 2 (SO 4 ) 3 ・H 2 O, Al(H 2 P.O. 4 ) 3 , C 2 H 5 O 4 Al, Al 2 (SO 4 ) 3 , NaAlO 2 , Al 2 CoO 4 , LaAlO 3 , and MgAl 2 O 4 The method for producing a positive electrode active material according to claim 1 , wherein the positive electrode active material is one or more selected from the group consisting of:

5. The method for producing a positive electrode active material according to any one of claims 1 to 4, wherein the heat treatment temperature is 250°C to 400°C.

6. The boron-containing source material is H 3 B.O. 3 , B 2 H 4 O 4 , B 2 O 3 , LiBO 2 , Li 2 B 4 O 7 and AlBO 3 The method for producing a positive electrode active material according to claim 1 , wherein the positive electrode active material is one or more selected from the group consisting of:

7. The present invention includes a lithium transition metal oxide represented by the following formula 2, and a coating layer containing boron formed on a surface of the lithium transition metal oxide, the coating layer comprises a Li-Al-B-O solid solution; The intensity of the peak detected at a mass of more than 27.0 and less than 27.5 in the time-of-flight secondary ion mass spectrometry spectrum and Al + A positive electrode active material having a peak intensity ratio of 1:0.5 to 1:1.5: [Chemical formula 2] Li x Ni a2 Co b2 Mn c2 Al d2 M 1 e2 O 2 In the above Chemical Formula 2, M 1 is one or more selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, Ce, Hf, F, P, S and La, 0.9≦x≦1.12, 0.7≦a2≦1.0, 0≦b2≦0.3, 0≦c2≦0.3, 0<d2≦0.2, and 0≦e2≦0.

1.

8. The ratio of the intensity of the peak detected at 182 mass to 184 mass in the time-of-flight secondary ion mass spectrometry spectrum of the positive electrode active material to the intensity of the peak detected at 172 mass to 174 mass is 1:0.3 to 1:

2. The positive electrode active material according to claim 7.

9. The ratio of the intensity of the peak detected at 182 mass to 184 mass in the time-of-flight secondary ion mass spectrometry spectrum of the positive electrode active material to the intensity of the peak detected at 197 mass to 199 mass is 1:0.3 to 1:1.

5. The positive electrode active material according to claim 7 or 8.

10. A positive electrode for a lithium secondary battery, comprising the positive electrode active material according to claim 7 .

11. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 10.

Citation Information

Patent Citations

  • Positive active material for lithium secondary battery and its manufacturing method

    JP2009266712A

  • Positive electrode active material for secondary battery, and secondary battery

    WO2020162277A1